Proposed new design scheme of Comic Centre for Comixtra No 32, Jalan 22/14, Section 14, 55100 Petaling Jaya, Selangor / Siti Kamariah Jasmani - Jasmani, Siti Kamariah (Faculty of Architecture, Planning and Surveying, 2005)
Comic generally means a sequence of pictures that tell stories. It is one of the printed medium that sometimes can influence people mostly teenagers in good and bad way. In fact, comics are tremendously popular in both east and west. Both of these cultures already accepted this medium since centuries ago. It is often surprised readers with something amazingly and always contents with lots of impact to young generation’s mind. Comics are not just for young people, but adult do enjoy comics on trains, coffee shop and at work. In addition, it is also a basic entertainment medium besides electronic media for part of the society to enjoy their life and help them to release and escape from tension and stress. There are so many type of comics that sometimes it can be characterized by garishly dressed superheroes, is actually as diverse as the genres and subgenres found in comics. It runs the gamut from horror to documentary. From their humble beginnings as anthologies of comic strips in newspapers, comics have progressed into a highly sophisticated, and still evolving, literary art form with talented writer such as Hayoa Miyazaki and the like.Equally important is the vat array of luminaries of highly talented artist like Osamu Tezuka, Ma Wing Shing, Gayour, and the like - just to name a few - who have enabled comic art to be catapulted into the art galleries as recognition of the distinguished quality of artistic input.